PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR POS (PERSERO) PAINAN PESISIR SELATAN - Mutia Wulandari; Delvianti; Agussalim M (LPPM Universitas Ekasakti, Padang, 2021)
The results of this study aim to examine and analyze the influence of organizational culture on the performance of South Painan Post Office employees (Persero) where Variable X is the Post Office (Persero) Organizational Culture of South Painan Coastal The dependent variable is the Employee Performance of South Painan Post Office (Persero). This study uses the Classic Assumption Test which consists of the Normality Test, the Heroskadisity Test and the Simple Regression Test, the t Test. The results of this study are partially Organizational Culture Variables and Positive Significant Influence on the Performance of Post Office (Persero) Painan Pesisir Selatan and TCR Organizations Post Office (Persero) Organizations South Painan is the Highest Personality and TCR Employee Performance Post Office (Persero) Painan The highest South Coast is the Achievement at the Painan South Coast Post Office (Persero)